"Bacon Bacon Bacon": Food-Related Tweets and Sentiment in Metro Detroit - Vydiswaran, V. G.; Romero, Daniel; Zhao, Xinyan; Yu, Deahan; Gomez-Lopez, Iris; Lu, Jin; Iott, Bradley; Baylin, Ana; Clarke, Philippa; Berrocal, Veronica; Goodspeed, Robert; Veinot, Tiffany (Proceedings of the International AAAI Conference on Web and Social Media, 2018)
Initiatives to reduce neighborhood-based health disparities require access to meaningful, timely, and local information regarding health behavior and its determinants. In this paper, we examine the validity of Twitter as a source of information for analysis of dietary patterns and attitudes. We analyze the "healthiness" quotient of food-related tweets and sentiment regarding those tweets from metropolitan Detroit. Our findings demonstrate feasibility of using Twitter to understand neighborhood characteristics regarding food attitudes and potential use in studying neighborhood-based health disparities.